Nursing and care of pre-born - Gurinskaitė, Laura; Jurgelevičiūtė, Kristina; Grušnytė, Kamilė; Jakelytė, Lukrecija; Joskaudaitė, Greta; Gierasimovič, Zita (Slauga. Mokslas ir praktika, 2020)
Premature birth is a birth that takes place before the end of the 37th week of pregnancy. Premature birth is one of the most frequent child-birth related complications manifesting itself in 5-18% of pregnancy cases in the world. Risks of premature birth are divided into two groups: medical factors and factors related to the lifestyle of the pregnant woman. It is important for women to recognise the warning signs of premature birth because then there is a possibility to preserve the foetus. Premature babies have underdeveloped organs, and this requires nursing and treatment in the Intensive Therapy Unit. Nursing of premature babies requires highly qualified staff. In the course of seven years (between 2010 and 2017) the premature birth rate was on the increase, however, in places where medical care of specialists is not easily available, women in child-birth run a greater risk of complications. The situation of premature births in Lithuania is similar to that in European countries; only the number of still-born premature babies decreased in 2017. Frequent risk factors of premature births are as follows: medical factors related to the mother’s health, the lifestyle of the pregnant woman, pregnancy at an early age, when a woman is older than 35. Nursing of premature babies requires high qualification and is directed towards characteristic changes in physiological functions of the organism: breathing, arterial blood pressure, maintenance of temperature, feeding. The nursing staff teach the mother to look after her premature baby.